‘Save the Adulteress!’ Ancient Jewish Responsa in the Gospels? - Young, Brad H. (New Testament studies, 1995)
The gospel story of the Woman Caught in Adultery (John 7.53–8.11), has captured the hearts of many listeners because it stirs up strong feelings of compassion for a human being in a vulnerable situation, even someone who has betrayed his or her marriage vow and committed a serious wrong. The love, acceptance and forgiveness of Jesus as well as his profound wisdom as a respected teacher come out of the narrated scene. Jesus answers a question that solves a very severe problem. These elements of the dramatic episode from the life of Jesus are clear. The Jewish people in the story, however, are viewed as antagonists. The Pharisees threaten the woman's life and seek to accuse Jesus. Silhouetted against the passion, this accusation might even be viewed by some readers as a charge to bring about the death of Jesus. Is this the only possible interpretation of the Pharisees' role in the gospel story?